Panoramic view of MDH1: driving cancer progression and shaping the tumor immune microenvironment - Lou, Yunchen; Lou, Yunwei; Cheng, Yao; Xu, Beining; Chen, Hanbin; Dai, Yinwei (Frontiers in Immunology, 2025)
BackgroundMalate dehydrogenase 1 (MDH1), an NAD(H)-dependent isoenzyme, is a key component of the malate-aspartate shuttle (MAS). A significant association has been observed between MDH1 expression and various characteristics of the tumor microenvironment across different cancer types.MethodsThis study provides comprehensive pan-cancer analyses exploring the expression patterns, clinical and pathological correlations, genetic alterations, immunogenomic profiles, single-cell dynamics, alternative splicing signatures, and pharmacological sensitivities related to MDH1. Drug sensitivity profiling and molecular docking techniques have been employed to identify potential anti-cancer compounds targeting MDH1. Experiments have also been conducted to investigate the biological function of MDH1 in lung adenocarcinoma (LUAD) and to confirm the interaction between MDH1 and macrophages using immunofluorescence assays.ResultsMDH1 expression levels are elevated across a wide range of malignancies, and overexpression of MDH1 was consistently linked to poor prognosis in multiple cancer subtypes. Moreover, MDH1 expression shows complex correlations with various immune cell populations, particularly macrophages, and cohort analysis of both bulk and pan-cancer single-cell immunotherapy data suggest that MDH1 could serve as a predictive marker for immunotherapy responses. Moreover, knockdown of MDH1 suppresses macrophage invasion. To investigate the role of MDH1 in LUAD cells, a potential inhibitor of MDH1 was identified, BI-2536, and has been confirmed to impact MDH1 activity and impede the growth of LUAD cells.ConclusionOur findings indicate that MDH1 may serve as a potential prognostic marker and a promising target for cancer immunotherapy.